Outpatient Clinic Management System at Adventist Medical Center Bacolod - Diplomo, Junic B.; Pomperada, Jake R.; Madrigal, Dennis V. (Technium Social Sciences Journal, 2025)
The increasing demand for efficient and secure healthcare systems calls for innovative digital solutions [1]. This capstone project presents the development of an Outpatient Clinic Management System for Outpatient Department of Adventist Medical Center Bacolod, aiming to transition from a paper-based process to a hybrid web-based and desktop-based system application. The system is designed to streamline clinical operations, improve patient record management, and support administrative decision-making [2]. The system ensures the accurate and secure handling of medical data while reducing manual workloads [3]. The system project will undergo thorough testing and evaluation to guarantee the reliability and security of patient demographic data [4]. Sufficient training and continuous support will be available to ensure optimal system utilization [5]. Resistance to change and insufficient training could hinder user adoption and system efficacy [6]. Comprehensive documentation, comprising user manuals and technical specifications, is vital for guiding users throughout the project [4]. A rapid application development model helps the developer quickly deliver the system project to the customer [7]. This project's development was guided by the Gantt chart, which outlines the timeline schedule for system development [8]. Higher or minimum requirements for hardware devices are essential to ensure the system's seamless operation [4]. Vulnerability in patient data security and breaches of confidentiality are vital in this project [9]. The hospital complies with data protection regulations. The Clinic Management System significantly improves workflow efficiency and data management within the clinic. It reduces human error, enhances patient service, and provides actionable insights through comprehensive reporting and data analytic visualization. By digitizing core processes such as appointment scheduling, consultation, prescription, ordering, and recordkeeping, the system streamlines clinical operations and supports timely, informed decision-making [3]. The system’s modular design allows for easy maintenance and scalability, making it adaptable to future requirements and healthcare innovations [4]. Its user-friendly interface and reliable functionality increase staff productivity and reduce administrative burden [4]. The integration of features such as audit trails and automated email notifications further contributes to operational transparency and improved patient engagement [4]. To keep the OPD Clinic Management System efficient and future-ready, regular updates, system expansions, and strong technical support are recommended [10].